Frustrated Lewis Pairs as Molecular Receptors: Colorimetric and Electrochemical Detection of Nitrous Oxide1. Issue 52 (12th November 2013) - Kelly, Michael J.; Gilbert, Jessica; Tirfoin, Remi; Aldridge, Simon
<x xml:space="preserve">Abstract</x> Laughing about frustration: Frustrated Lewis pairs comprising a bulky tertiary phosphine and a strongly Lewis acidic ferrocenyl borane (FcB(C6F5)2) have been investigated for the colorimetric/electrochemical detection of N2O. One such system, based on tBu3P/FcB(C6F5)2, not only signals the presence of N2O, but also has the ability to differentiate between N2O and O2.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>